Gerakan SADARI DMG (Sadar dan Deteksi Risiko Diabetes Melitus Gestasional) pada Ibu hamil di Komunitas - Dwi Lestari, Yusri; Nur Rohmatul Ummah; Nur Azizah Rofiyah; Revilia Ine Aulia Sabila (Health Care : Journal of Community Service, 2025)
Gestational diabetes (GDM) is one of the pregnancy complications characterized by glucose intolerance that first appears during pregnancy. This condition not only increases the risk of complications such as preeclampsia, preterm labor, and macrosomia, but also has long-term effects on both the mother and baby, including a higher risk of developing type 2 diabetes later in life. The PKM SADARI GDM Movement (Awareness and Risk Detection of Gestational Diabetes) aims to improve the knowledge and awareness of pregnant women in the community regarding the risks and prevention of gestational diabetes mellitus (GDM), as well as to promote early detection through educational approaches and simple screening. This community service program is carried out through several methods, including interactive education and outreach on GDM, physical activity training using prenatal yoga as a non-pharmacological preventive measure, risk screening using questionnaires and random blood glucose testing, and continuous assistance and monitoring throughout the program. The solutions offered include the provision of easy-to-understand information, early risk detection, and the implementation of a healthy lifestyle that can be independently practiced with the support of local health workers. In conclusion, the SADARI GDM movement serves as an effective and applicable strategy to increase pregnant women's awareness of the importance of GDM prevention through education, early detection, and structured physical activity, and it has the potential to become a sustainable promotive and preventive effort at the community level.